Physical and chemical properties importance of Rose hip (R. canina, R. rubiginosa): a review - Espinoza, T. (2016)
Consumers increasingly demand products in their diets that not only provide the nutrients required for a healthy life, they are also preferably those that can complement with beneficial health properties. In recent decades it has been recognized rosehip, Rosa and Rosa canina the rubiginosa as fruits contain many nutraceutical properties. This paper reviews the research papers carried the Rosehip from the point of view of their importance of their consumption and their health benefits; describing the chemical, physical and biochemical characteristics such as content of phenolic compounds, fatty acids, linoleic acid, mineral; and other important also from an industrial point of view, such as antioxidants, pigments, among other compounds. According to the information collected, the Rosehip is a source of micronutrients including vitamin C and lycopene, also delivering a good nutritional value; by the above it should be considered a functional food. Although a species that grows wild on forest soils; still less fruit and herb its importance in the consumer must be considered.